2019
DOI: 10.1093/mnras/stz2163
|View full text |Cite
|
Sign up to set email alerts
|

Nulling at short wavelengths: theoretical performance constraints and a demonstration of faint companion detection inside the diffraction limit with a rotating-baseline interferometer

Abstract: The Palomar Fiber Nuller (PFN) is a rotating-baseline nulling interferometer that enables high-accuracy near-infrared (NIR) nulling observations with full azimuth coverage. To achieve NIR null-depth accuracies of several x 10 -4 , the PFN uses a common-mode optical system to provide a high degree of symmetry, single-mode-fiber beam combination to reduce sensitivity to pointing and wavefront errors, extreme adaptive optics to stabilize the fiber coupling and the cross-aperture fringe phase, rapid signal calibra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…This observing mode takes advantage of the spatial filtering provided by the resolving power of each of the 8 m telescopes of the Very Large Telescope Interferometer (VLTI), coupled into single mode fibers to reach the required contrast. Interferometric nullers (Bracewell 1978;Colavita et al 2009;Serabyn et al 2019;Hoffmann et al 2014;Defrère et al 2015;Norris et al 2020) offer the possibility to explore smaller angular separations through the use of fragmented apertures and long-baseline interferometry. Some combining solutions have been found that optimize the rejection of resolved stars (Angel & Woolf 1997;Guyon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This observing mode takes advantage of the spatial filtering provided by the resolving power of each of the 8 m telescopes of the Very Large Telescope Interferometer (VLTI), coupled into single mode fibers to reach the required contrast. Interferometric nullers (Bracewell 1978;Colavita et al 2009;Serabyn et al 2019;Hoffmann et al 2014;Defrère et al 2015;Norris et al 2020) offer the possibility to explore smaller angular separations through the use of fragmented apertures and long-baseline interferometry. Some combining solutions have been found that optimize the rejection of resolved stars (Angel & Woolf 1997;Guyon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By operating at the null phase, the noise is minimal in comparison to standard interferometry. 40 This null depth can be decomposed as a timeaveraged null depth N in the presence of active OPD matching and intensity balancing, and an RMS fluctuation of the null level σ N . 39 The time-averaged null depth of a Bracewell interferometer observing a single star is given by E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 2 ; 1 1 6 ; 4 8 6…”
Section: Null Depthmentioning
confidence: 99%
“…These two improvements on traditional nulling interferometry have allowed PFN to demonstrate on-sky null depths of ∼ 10 −3 in the past 9,10 and more recently of ∼ 10 −4 with the detection of a faint companion well within the diffraction limit of the Palomar Telescope. 11 Building on this heritage, Vortex Fiber Nulling (VFN) is a new fiber nulling technique introduced by our team in 2018. 12 It is very similar to the PFN in that it relies on a pupil mask and SMF but instead of creating two Figure 1.…”
Section: Introductionmentioning
confidence: 99%